Two different sources of Perlecan cooperate for its function in the basement membrane of the Drosophila wing imaginal disc. Issue 4 (11th December 2020) - Bonche, Raphaël; Chessel, Aline; Boisivon, Séverine; Smolen, Prune; Thérond, Pascal; Pizette, Sandrine
Abstract: Background: The basement membrane (BM) provides mechanical shaping of tissues during morphogenesis. The Drosophila BM proteoglycan Perlecan is vital for this process in the wing imaginal disc. This function is thought to be fostered by the heparan sulfate chains attached to the domain I of vertebrate Perlecan. However, this domain is not present in Drosophila, and the source of Perlecan for the wing imaginal disc BM remains unclear. Here, we tackle these two issues. Results: In silico analysis shows that Drosophila Perlecan holds a domain I. Moreover, by combining in situ hybridization of Perlecan mRNA and protein staining, together with tissue‐specific Perlecan depletion, we find that there is an autonomous and a non‐autonomous source for Perlecan deposition in the wing imaginal disc BM. We further show that both sources cooperate for correct distribution of Perlecan in the wing imaginal disc and morphogenesis of this tissue. Conclusions: These results show that Perlecan is fully conserved in Drosophila, providing a valuable in vivo model system to study its role in BM function. The existence of two different sources for Perlecan incorporation in the wing imaginal disc BM raises the possibility that inter‐organ communication mediated at the level of the BM is involved in organogenesis. Key Findings: Drosophila perlecan is fully conserved since it contains sequences encoding a domain I with consensus sites for heparan sulfate chains attachment A new autonomous source for Perlecan production is identified in the wing imaginal disc The Perlecan deposited in the basement membrane of the wing imaginal disc is autonomously and non‐autonomously produced The autonomous source partially compensates for the non‐autonomous one in Perlecan deposition in the wing imaginal disc basement membrane The two Perlecan sources are redundant for Perlecan function in wing imaginal disc morphogenesis